2020
DOI: 10.1093/jamia/ocaa198
|View full text |Cite
|
Sign up to set email alerts
|

Different roles with different goals: Designing to support shared situational awareness between patients and clinicians in the hospital

Abstract: Objective Team situational awareness helps to ensure high-quality care and prevent errors in the complex hospital environment. Although extensive work has examined factors that contribute to breakdowns in situational awareness among clinicians, patients’ and caregivers’ roles have been neglected. To address this gap, we studied team-based situational awareness from the perspective of patients and their caregivers. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The IRT process led to findings supported by previous research in the area of care transitions indicating health systems need centralized and shareable sources of information tailored to support situation awareness among healthcare providers and patients in real-time. 24 Previous research regarding situation awareness has focused on inpatient settings and shown improved outcomes for patients with the implementation of periodic information checkpoints and regular information sharing between providers. 25,26 Since hospital-to-HH care transitions are challenging periods for information transfer, increasing situation awareness can support HH clinicians to deliver informed care, identify high-risk transitions, and improve discharge planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IRT process led to findings supported by previous research in the area of care transitions indicating health systems need centralized and shareable sources of information tailored to support situation awareness among healthcare providers and patients in real-time. 24 Previous research regarding situation awareness has focused on inpatient settings and shown improved outcomes for patients with the implementation of periodic information checkpoints and regular information sharing between providers. 25,26 Since hospital-to-HH care transitions are challenging periods for information transfer, increasing situation awareness can support HH clinicians to deliver informed care, identify high-risk transitions, and improve discharge planning.…”
Section: Discussionmentioning
confidence: 99%
“…While clinicians have specific expertise to identify healthcare-related safety concerns, incorporating patient voices into quality reporting supports communication with those who have the most to gain from successful situational awareness – patients themselves. 24 Additionally, since the onset of the COVID-19 pandemic, there has been a coordinated effort within the HH industry to continue to provide quality care safely to people in their homes despite the risks associated with close contact between patients and HH clinicians. 27 Care coordination challenges presented by the pandemic highlight the importance of a tool for HH agencies to identify potential threats to patient safety in real-time.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of SSA is no stranger to medical settings or public health. It was applied to analyzing the impact of dialogues in surgery rooms on clinical decision-making (Gillespie et al, 2013), and informing the design of health information technologies to improve patients' hospital experiences (Pollack et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It refers to the degree to which the actors in the system have the same understanding (Endsley, 1995;Endsley & Jones, 1997). It has three levels: 1) "the perception of elements in the environment within a volume of time and space" (Endsley, 1988); 2) "the comprehension of their meaning" (Endsley, 1988); and, 3) projection of their status and the prediction of their actions on the shared goals in the future (Endsley, 1988;Pollack et al, 2021). The concept of SSA is no stranger to medical settings or public health.…”
mentioning
confidence: 99%
See 1 more Smart Citation